Determinants of foreign currency hedging by UK firms: the panel data evidence - Nguyen, Tuan Thanh (2016)
This study examines the factors that prompt firms to hedge against exchange rate risks based on a sample of UK FT 500 non-financial firms. Using a panel data collected over a 11-year period from 2005 to 2015, the study finds that firms hedge their foreign currency exposure in respond to factors including scale economies in costs, liquidity and leverage. While the conclusion regarding economies of scale is robust to the exclusion of other risk hedger in the sample and the use of conventional definition of hedging, the proxies measuring liquidity and leverage appear to be inconsistent in both robustness tests. Another finding is that firms tend to hedge more when their degree of exposure and dividend payment are higher.